A low-diversity Peruvispira-dominated gastropod assemblage from the Permian Ratburi Group of Central Thailand. Issue 2 (3rd April 2022) - Karapunar, Baran; Nützel, Alexander; Ketwetsuriya, Chatchalerm
Abstract: Permian gastropods from Thailand have been extensively studied over the last few years. The earliest known fossil collection was recovered in 1967 but has never been figured or described. Here, we document this historically important gastropod assemblage excavated from the upper-Lower to Middle Permian Ratburi Group of Khao Mang Lat in the Ban Kao District of Kanchanaburi Province, Central Thailand. The material comprises approximately 200 specimens, almost all of which represent a new species, Peruvispira kanchanaburiensis sp. nov. (Goniasmatidae), together with a single individual of Orthonychia sp. (Orthonychiidae = Platyceratidae). This exceptionally low-diversity community is unusual in comparison to Permian gastropod faunas reported from elsewhere, and could reflect either a low temperature palaeoenvironmental setting or priority effects resulting from early establishment of planktotrophic larvae within the local habitat. Baran Karapunar [karapunar@snsb.de ], SNSB-Bayerische Staatssammlung für Paläontologie und Geologie, Richard-Wagner-Str. 10, 80333 München, Germany, and Department of Earth and Environmental Sciences, Paleontology & Geobiology, Ludwig-Maximilians-Universität München, Richard-Wagner-Str. 10, 80333 München, Germany; Alexander Nützel [nuetzel@snsb.de ], SNSB-Bayerische Staatssammlung für Paläontologie und Geologie, Richard-Wagner-Str. 10, 80333 München, Germany, and Department of Earth and Environmental Sciences, Paleontology & Geobiology, Ludwig-Maximilians-Universität München, Richard-Wagner-Str. 10, 80333 München, Germany, and GeoBio-Center, Ludwig-Maximilians-Universität München, Richard-Wagner-Str. 10, 80333 München, Germany; Chatchalerm Ketwetsuriya [ketwetsuriya.c@gmail.com ], Department of Earth Sciences, Faculty of Science, Kasetsart University, 10900 Bangkok, Thailand .